2014
DOI: 10.1371/journal.pone.0099894
|View full text |Cite
|
Sign up to set email alerts
|

A New F131V Mutation in Chlamydomonas Phytoene Desaturase Locates a Cluster of Norflurazon Resistance Mutations near the FAD-Binding Site in 3D Protein Models

Abstract: The green alga Chlamydomonas reinhardtii provides a tractable genetic model to study herbicide mode of action using forward genetics. The herbicide norflurazon inhibits phytoene desaturase, which is required for carotenoid synthesis. Locating amino acid substitutions in mutant phytoene desaturases conferring norflurazon resistance provides a genetic approach to map the herbicide binding site. We isolated a UV-induced mutant able to grow in very high concentrations of norflurazon (150 µM). The phytoene desatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…Although CRTI from Pantoea ananatis and OsPDS share only 22% amino acid sequence similarity and 11% identity, much of which is attributed to the FAD-binding Rossmann fold common to both, and although there are clear differences in catalysis, like the differential roles of oxygen, quinones, stereochemistry and the number of double bond introduced, the overall protein folds are quite similar. This places OsPDS and CRTI into a structural context with monoamine oxidases and protophorphyrinogen oxidases as suggested previously based on sequence comparisons of extended Rossman fold domains [ 51 ] and homology modeling [ 52 ]. This implies that that the two desaturases have evolved divergently or convergently resulting in two different approaches towards achieving similar catalytic goals.…”
Section: Discussionsupporting
confidence: 53%
“…Although CRTI from Pantoea ananatis and OsPDS share only 22% amino acid sequence similarity and 11% identity, much of which is attributed to the FAD-binding Rossmann fold common to both, and although there are clear differences in catalysis, like the differential roles of oxygen, quinones, stereochemistry and the number of double bond introduced, the overall protein folds are quite similar. This places OsPDS and CRTI into a structural context with monoamine oxidases and protophorphyrinogen oxidases as suggested previously based on sequence comparisons of extended Rossman fold domains [ 51 ] and homology modeling [ 52 ]. This implies that that the two desaturases have evolved divergently or convergently resulting in two different approaches towards achieving similar catalytic goals.…”
Section: Discussionsupporting
confidence: 53%
“…The synthetic tp CRTIop gene allowed for norflurazon-based selection of transformants with no background of spontaneous herbicide-resistant clones. The level of resistance to norflurazon acquired by the C. reinhardtii transformed with CRTIop is of the same order as the resistance reported by Suarez et al [28] or Bruggeman and coworkers [12], who found 30- and 40-fold increases, respectively, in the tolerance to norflurazon for transgenic Chlamydomonas harbouring modified versions of its own PDS gene. Similar strategies using mutated PDS versions and norflurazon have been successfully used for the selection of other transformed microalgae species, such as Haematococcuspluvialis [29,30], Chlorella zofingiensis [31,32], or Isocrhrysis [33].…”
Section: Resultssupporting
confidence: 83%
“…Samples from C. reinhardtii cultures, grown in TAP liquid medium supplemented with 1.5 µg mL of norflurazon in the same conditions described in Section 3.1., were used for the extraction of carotenoids with methanol as described by Linchtehaler [42]. The chromatographic analysis was performed in a Merck Hitachi HPLC equipped with a diode array detector as described by Young and coworkers [28] using an RP-18 column, a flow rate of 1mL min −1 , and a final injection volume of 100 µL. Two mobile phases were used: Solvent A (ethyl acetate 100%) and solvent B (acetonitrile:H 2 O; 9:1 v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Mutagens can be used to generate mutants Mutagens have been used to generate mutants with aberrations in photosynthesis and carbon fixation (Eversole, 1956;Levine, 1960a,b;Bennoun and Levine, 1967), motility (Randall et al, 1964;Warr et al, 1966), mating (Goodenough et al, 1976), nitrogen assimilation (Ebersold, 1956;Eversole, 1956), respiration (Wiseman et al, 1977), and in a variety of biosynthetic pathways (Eversole, 1956), in addition to mutants resistant to herbicides (Galloway and Mets, 1984;Hartnett et al, 1987;Kataoka et al, 1990;Lux and Dutcher, 1991;Oshio et al, 1993;Vartak and Bhargava, 1997;Randolph-Anderson et al, 1998;Suarez et al, 2014), antibiotics (Sager, 1954;Mets and Bogorad, 1971), and inhibitors (Nelson et al, 1994). For many forward genetic screens, the use of mutagens instead of insertional mutagenesis may be preferred.…”
Section: Generating and Mapping Mutants In The Nuclear Genome With Mumentioning
confidence: 99%